2016
DOI: 10.1111/ijcs.12293
|View full text |Cite
|
Sign up to set email alerts
|

Black urban consumers’ status consumption of clothing brands in the emerging South African market

Abstract: Status concerns are noteworthy within a modern society as it is a key feature of individuals' social reputation. Engaging in this form of thinking results in particular patterns of consumption within consumer groups. In South Africa, Black urban consumers have newfound spending power and social mobility. This study investigated motivators of Black urban consumers' status consumption across different demographic variables (age, income and profession) in the South African (SA) emerging market. A survey research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 52 publications
1
28
1
Order By: Relevance
“…The fact that consumption of a brand adds to consumers' image in their social circles, enhances their role and positively contributes to their social status strengthens consumer-brand ties, as highlighted in previously conducted studies but a different context (Cronje et al, 2016). The consumption of brands offers rural customers an opportunity to seek some social status in a close, socially visible, and connected society such as Pakistan (Dev et al, 2018).…”
Section: Mediation Effectmentioning
confidence: 76%
See 2 more Smart Citations
“…The fact that consumption of a brand adds to consumers' image in their social circles, enhances their role and positively contributes to their social status strengthens consumer-brand ties, as highlighted in previously conducted studies but a different context (Cronje et al, 2016). The consumption of brands offers rural customers an opportunity to seek some social status in a close, socially visible, and connected society such as Pakistan (Dev et al, 2018).…”
Section: Mediation Effectmentioning
confidence: 76%
“…Once consumers derive this value from brands, the positive emotion of love might be aroused. Consequently, consumers can serve their esteem needs while being acknowledged by the members of the reference group, adding to their social status (Cronje et al, 2016).…”
Section: Self-expression and Brand Love Among Rural Customersmentioning
confidence: 99%
See 1 more Smart Citation
“…It was further reported that the African consumers in SA are driven to use luxury goods to display flamboyance and to symbolise success and accomplishments, which is shared with others (Atwal & Bryson, 2014). However, Cronje et al (2016) found that luxury brands purchase behaviour of black consumers does not differ across gender of consumers. This shows that there are contradicting findings with regard to the effect of gender on luxury brands purchase since Roux a , Tafani & Vigneron (2017:108) also found that gender influence luxury brands purchase and that male and females consumers consider different factors when purchasing luxury brands.…”
Section: Empirical Reviewmentioning
confidence: 82%
“…However, many are brand-and status-conscious and their preference for international brands is higher than for local brands, which supports developed market economies rather than emerging market economies (Cronje, Jacobs & Retief 2016;Pavlić & Vukić 2019). South African Generation Z consumers' preference for international brands stem from the greater exposure of these brands, in comparison to local brands, on social media sites, which are commonly accessed using smartphones (Ayuni 2019;Cronje et al 2016). Despite their increased use of smartphones, only 30% South African Generation Z consumers make brand-related purchases online as compared with the global average of 61% (Fourie 2017;Stastista 2018;Thompson 2017).…”
mentioning
confidence: 99%